On the numerical solution of differential-algebraic equations - Aspoas, Michael A (My University, 2016)
We give an overview of the numerical solution of the initial value differential-algebraic equation (DAB) from the underlying theory, through both the development of numerical techniques and software and a survey of the major areas of application, to the implementation of available software codes in the solution of DABs arising in applications. The experimental part serves to demonstrate the need for specific DAB, rather than simply ordinary differential equation (ODE), methods and the special considerations requited for the successful numerical solution of DAEs, as well.as verifying predictions made in the theory. It is hoped that '.his dissertation can be used as a reference by those working in areas of application, or at least as a pointer to the relevant literature.
Keywords: Differential-algebraic equations.